The loving reciprocity scale: Internal structure, factorial invariance, reliability, and convergent validity - Nikolai M. Rodas-Vera (Acta Psychologica)
Loving reciprocity is the correspondence between love given and love received. Despite its importance, instruments for its measurement remain scarce, limiting scientific research and professional evaluation. This study examined several psychometric properties of a new instrument based on the Triangular Theory of Love: The Loving Reciprocity Scale (LRS). Specifically, we assessed content validity, internal structure, invariance, convergent validity, and reliability. To support convergent validity, we examined the relationships between reciprocity, love, well-being, and relationship satisfaction. Two groups of Peruvian adults were recruited (N1 = 240, N2 = 521) to evaluate the effectiveness of the LRS. The proposed 12-item instrument demonstrated strong content validity (Aiken's V > 0.70). A second-order model with three dimensions—reciprocal intimacy (ordinal α = 0.897), reciprocal commitment (ordinal α = 0.932), and reciprocal passion (ordinal α = 0.955)—showed excellent fit, with high internal consistency for the total scale (ordinal α = 0.953). The model was invariant across gender (female and male) and age groups (young adults and adults). Loving reciprocity was significantly and positively associated with the studied variables. These findings indicate that the LRS is a valid and reliable instrument suitable for use in both research and clinical practices.